A microfluidics assay to study invasion of human placental trophoblast cells. Issue 130 (31st May 2017) - Abbas, Yassen; Oefner, Carolin Melati; Polacheck, William J.; Gardner, Lucy; Farrell, Lydia; Sharkey, Andrew; Kamm, Roger; Moffett, Ashley; Oyen, Michelle L.
Abstract : Pre-eclampsia, fetal growth restriction and stillbirth are major pregnancy disorders throughout the world. The underlying pathogenesis of these diseases is defective placentation characterized by inadequate invasion of extravillous placental trophoblast cells into the uterine arteries. How trophoblast invasion is controlled remains an unanswered question but is influenced by maternal uterine immune cells called decidual natural killer cells. Here, we describe an in vitro microfluidic invasion assay to study the migration of primary human trophoblast cells. Each experiment can be performed with a small number of cells making it possible to conduct research on human samples despite the challenges of isolating primary trophoblast cells. Cells are exposed to a chemical gradient and tracked in a three-dimensional microenvironment using real-time high-resolution imaging, so that dynamic readouts on cell migration such as directionality, motility and velocity are obtained. The microfluidic system was validated using isolated trophoblast and a gradient of granulocyte-macrophage colony-stimulating factor, a cytokine produced by activated decidual natural killer cells. This microfluidic model provides detailed analysis of the dynamics of trophoblast migration compared to previous assays and can be modified in future to study in vitro how human trophoblast behaves during placentation.